2014
DOI: 10.3920/wmj2013.1640
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fungal contamination and mycotoxin production at workplaces in composting plants, tanneries, archives and libraries

Abstract: The aim of this research was to estimate fungal contamination at workplaces in composting plants, tanneries, libraries and archives. The influence of raw material processed or stored at these workplaces (compost, leather, cellulose) on the toxigenicity and cytotoxicity of fungi was also investigated. Qualitative and quantitative mycological analysis confirmed a high contamination in composting plants and tanneries, while materials in archives and libraries were less contaminated. Among the 74 fungal species pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Also in the authors' own study, moulds belonging to Aspergillus genus made up a significant percentage of the identified fungi, including A. fumigatus, which was observed in over a half of the isolates of this type. The fungi belonging to Aspergillus genus might present a significant threat to patients' health, especially those with impaired immunity, and particularly newborns [28,29,30]. They may also pose a threat to the staff working in these rooms because they are included in the group of 2 biological factors which may have negative effects on people exposed to them for prolonged periods [31].…”
Section: Discussionmentioning
confidence: 99%
“…Also in the authors' own study, moulds belonging to Aspergillus genus made up a significant percentage of the identified fungi, including A. fumigatus, which was observed in over a half of the isolates of this type. The fungi belonging to Aspergillus genus might present a significant threat to patients' health, especially those with impaired immunity, and particularly newborns [28,29,30]. They may also pose a threat to the staff working in these rooms because they are included in the group of 2 biological factors which may have negative effects on people exposed to them for prolonged periods [31].…”
Section: Discussionmentioning
confidence: 99%
“…P. brevicompactum was mainly characterized by mycophenolic acid production, while typical metabolites were identified for P. chrysogenum, as chrysogin, roquefortine C and secalonic acid D (Fischer et al, 2000;Frisvad et al, 2004;Gutarowska et al, 2014;Nielsen, 2003), together with andrastin A and B, citreorosein, fulvic acid, neoxaline and oxaline, typically produced by other Penicillium spp. Laatsch, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The air samples were collected by means of the impaction method with a flow rate of 140 l/min onto malt extract agar (MEA) supplemented with chloramphenicol (0.05%), using the Millipore Air Tester (MerckMillipore, USA). The samplers were placed at a height of 0.6-1.5 m above the floor, several occupational settings [4]. Additionally, there is no classification that would consider, on the one hand, fungal ability to disseminate and, on the other, the principal intake routes from their spores and metabolites taking into account each occupational setting.…”
Section: Conventional Methodologiesmentioning
confidence: 99%